2000
DOI: 10.1016/s0272-6963(00)00038-3
|View full text |Cite
|
Sign up to set email alerts
|

A typology of de‐coupling strategies in mixed services

Abstract: A typology of a class of service systems is proposed. The typology links strategic operational objectives to the decision to de‐couple work between the front and back offices of a service system. Four specific ideal types of a strategy/de‐coupling mix are described; each of which has distinct operational, marketing and human resource ramifications. A type that has had significant representation in traditional literature is the “Cost Leader” type, where back‐office activities are de‐coupled from the front offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 27 publications
9
139
0
Order By: Relevance
“…It focuses on the contingent relationship between the use of process design principles and the service strategy context of the firm. This framework is consistent with the work of several authors who have developed propositions linking the strategic context of the firm to the operational characteristics and design principles of the service organisation (Kellogg and Nie, 1995;Metters and Vargas, 2000). …”
Section: A Contingency-based Framework For Future Business Process Desupporting
confidence: 86%
See 3 more Smart Citations
“…It focuses on the contingent relationship between the use of process design principles and the service strategy context of the firm. This framework is consistent with the work of several authors who have developed propositions linking the strategic context of the firm to the operational characteristics and design principles of the service organisation (Kellogg and Nie, 1995;Metters and Vargas, 2000). …”
Section: A Contingency-based Framework For Future Business Process Desupporting
confidence: 86%
“…decoupled) and staffed with different employees. Zomerdijk and de Vries (2007) and Metters and Vargas (2000) studied task allocation in banking processes containing both customercontact and non-customer-contact work. These empirical studies have shown that diverse task allocation principles are appropriate to achieve different performance objectives under different strategic conditions.…”
Section: Assign Order To a Single Employeementioning
confidence: 99%
See 2 more Smart Citations
“…Chase advocates separating the front office, which is to focus on customers, from the back office, which is to be managed for cost reduction; this approach protects the technical core. Extending these works, Metters and Vargas (2000) empirically derive two distinct process configurations that rely on decoupling customer contact work from non-contact activities. The 'cost leader' decouples to lower costs while the 'focused professional' decouples to provide higher service.…”
Section: Implications For Theorymentioning
confidence: 99%